PERLINDUNGAN KONSUMEN ATAS RISIKO KEAMANAN INFORMASI DALAM TRANSAKSI E-COMMERCE - Nanin Koeswidi Astuti; Robertus Nugroho Perwiro Atmojo (Fakultas Hukum Universitas Kristen Indonesia, 2022)
This article analyzes consumer protection against the occurrence of information security risks in electronic transactions. The purpose of this article is to determine the risk relationship between the legal terms of agreement in e-commerce transactions and the terms of sale and purchase as regulated in the Civil Code, while regarding the risk of consumer information security in e-commerce. -Trade transaction agreements in order to provide for the parties, the ITE Law has regulated the system regulated in Article 20 paragraph (1) with a double-click system, so that the conditions for the validity of the agreement are for parties who have good intentions in the agreement. For e-commerce transactions that have high economic value, such as transactions worth tens to hundreds of millions of rupiah, the checks and balances mechanism can be considered as a safety net or a way to reduce risks arising from losses suffered by consumers.